International Environment: Recovery and Resolution Regimes as the Pillar of the Banking Union - Mejra Festić (Naše gospodarstvo/Our economy, 2019)
The purpose of the article is to present the possible regimes of bank resolution in the euro system and to highlight open questions concerning additional capital buffers and the valuation of assets according to the Bank Recovery and Resolution Directive (BRRD). The bail-in tool is used to write down or to convert certain liabilities with the purpose of restoring the capital adequacy. The valuation exercise would determine the amount of loss absorbtion to restore viability of the institution and capital adequacy. The bridge bank tool offers deeper restructuring powers to the competent resolution authority. Sale of the business tool is actually a variation of the bridge bank tool, enabling the resolution authority to transfer assets and liabilities to investors. The asset separation tool always is combined with another tool. The write-down is not a resolution tool, as it affects equity, while a bail-in tool goes further to other subordinated debt and senior debt. It is possible to establish additional resolution tools in the national legislation, as long as these tools are compatible with the principles of directive and national legislation in order to support cross-border group resolution. The issue of bank overregulation and the ability to meet the requirements without negative effects on the economy is emphasized.